Auto Transplantation – A Viable Option of Saving Teeth - Chopra, Viresh; Chopra, Harneet; Singh, Gurdeep; Comert, Fugen Dagli (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
The technique of Tooth auto transplantation for saving the tooth has a long-standing history. Third molars are most used as the donor teeth. A review of the current literature was undertaken with particular attention to the use of the third molar as the donor tooth. Appropriate patient selection is the key factor in the success of the technique. Other prognostic factors also play role in better healing and ultimate success of the whole technique. The findings from the available literature suggest that auto transplantation is a viable and cost-effective technique. However, the literature relating to the use of third molars as donor teeth for auto transplantation is limited and there are currently no evidence-based guidelines or protocols relating to the technique. This chapter discusses the option of auto transplantation to save teeth, their indication supported with a clinical case. It also discusses the protocols that authors implement for auto transplantation of wisdom teeth.